Esposito's temporality of finance: Endogeneity and revisability in derivative transactions - Conor Husbands (Finance and Society, 2020)
Recent years have seen greater interest in the theoretical foundations of abstract finance and their intersection with questions of philosophy and sociology. In particular, exchanges between authors such as Donald MacKenzie, Timothy Johnson, Elie Ayache, and others have debated the deterministic or contingent dynamics of markets, as well as their interdependency with the theories that purport to describe them. Working in this tradition, Elena Esposito raises a novel question in her 2011 book, The Future of Futures: could the exchange of derivative securities within financial markets entail, not so much the provision of liquidity, but the transaction of time? In this article, I reconstruct Esposito's analysis, arguing that the proper response to this question should be affirmative. Particular emphasis is laid on what I take to be the two fundamental and controversial premises which support this argument: first, the endogeneity of time-relations involved in financial markets; and second, the revisability of these time-relations. The advantage of recasting Esposito's position in this way is the defence it enables against various criticisms articulated in theory and philosophy circles, such as those of Ray Brassier. Finally, I discuss the significance of Esposito's theory, not only for this class of financial transactions, but also for certain issues in the philosophy of time.
Keywords: 300; Finance; temporality; derivatives; philosophy of markets; Elena Esposito; Ray Brassier